Thoracic NUT carcinoma: Common pathological features despite diversity of clinical presentations. (August 2021) - Fekkar, Amal; Emprou, Camille; Lefebvre, Christine; Ferretti, Gilbert; Stephanov, Olivier; Pissaloux, Daniel; Mc Leer, Anne; Toffart, Anne-Claire; Rousseaux, Sophie; Khochbin, Saadi; Lantuejoul, Sylvie; Valmary-Degano, Séverine
Highlights: The diagnosis of NUT carcinoma should be considered in all undifferentiated thoracic tumour infiltrated by neutrophils. Once considered, the diagnosis can be easily made by immunohistochemistry using a highly sensitive and specific antibody. Prognosis of NUT carcinoma remains extremely poor, but targeted therapies seem promising in BRD4-NUTM1 variant. Abstract: NUT carcinoma (NC), formerly known as NUT midline carcinoma, is a rare and very aggressive cancer. It is genetically defined by the presence of acquired chromosomal rearrangement of the NUTM1 (NUclear protein in Testis Midline carcinoma family member 1) gene at chromosome 15q14 with a member of the bromodomain-containing protein (BRD) family gene, usually BRD4. Although primarily reported in the head and neck, and mediastinum locations of younger individuals, it is now established that NC arises in multiple sites in patients of all ages, with no gender predilection. NC is very likely to be underdiagnosed because of a lack of awareness of both clinicians and pathologists on the one hand, and of a nonspecific histological presentation on the other hand. As it is indistinguishable from other poorly differentiated carcinomas, pathologists should consider NC as a differential diagnosis of any poorly differentiated tumour. Diagnosis is now easily made by immunohistochemistry, using a highly sensitive and specific NUT monoclonal antibody. Despite chemo- or chemo-radiotherapy, the prognosis of this tumour remains very poor. We report here a series of 3 cases of NC with different clinical and pathological presentations in order to draw attention on some common morphological features that can help clinicians and pathologists to think about this rare entity.